In silico ligand binding studies of cyanogenic beta-glucosidase, dhurrinase-2 from Sorghum bicolor - Mahajan, Chavi; Patel, Krunal; Khan, Bashir Mohammad; Rawal, Shuban S. (Journal of Molecular Modeling, 2015)
Dhurrinase, a cyanogenic beta-glucosidase from Sorghum bicolor is the key enzyme responsible for the hydrolysis of dhurrin to produce toxic hydrogen cyanide, as a part of plant defence mechanism. Dhurrinase 1 (SbDhr1) and dhurrinase 2 (SbDhr2), two isozymes have been isolated and characterized from S. bicolor. However, there is no information in the literature about the three dimensional (3D) structure of SbDhr2 and molecular interactions involved between the protein and ligand. In this study, the three dimensional structure of SbDhr2 was built based on homology modeling by using the X-ray crystallographic structure of its close homologue SbDhr1 as the template. The generated 3D model was energy minimized and the quality was validated by Ramachndran plot, various bioinformatic tools and their relevant parameters. Stability, folding-unfolding and flexibility of the modeled SbDhr2 was evaluated on the basis of RMSD, radius of gyration (R-g) and RMSF values respectively, obtained through molecular dynamic (MD) simulation. Further, molecular docking was performed with its natural substrate dhurrin, one substrate analogue, three un-natural substrates, and one inhibitor. Analysis of molecular interactions in the SbDhr2-ligand complexes revealed the key amino acid residues responsible to stabilize the ligands within the binding pocket through non-bonded interactions and some of them were found to be conserved (Glu239, Tyr381, Trp426, Glu454, Trp511). Reasonably broader substrate specificity of SbDhr2 was explained through the wider entrance passage observed in comparison to SbDhr1.
Keywords: beta-Glucosidase; Dhurrinase; Molecular docking; Molecular dynamic simulation; Sorghum bicolor

Effect of the amino acid L-histidine on methane hydrate growth kinetics - Bhattacharjee, Gaurav; Choudhary, Nilesh; Kumar, Asheesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Natural Gas Science and Engineering, 2016)
In the present study, the effect of a polar amino acid, L-histidine on methane hydrate growth kinetics has been investigated. Methane hydrate formation experiments were carried out in a stirred tank reactor setup at pressure and temperature conditions of 274.15 K and 5.0 MPa respectively. Two different concentrations (0.1 and 1 wt %) of L-histidine were studied. Hydrate growth through molecular dynamic (MD) simulation was also studied; pressure and temperature conditions for the simulations were set at 10.0 MPa and 270.0 K, while the concentration of L-histidine was kept fixed at 0.94 wt %. Hydrate formation runs using MD simulation were carried out with optimal concentration of methane in water. The presence of L-histidine in the system was found to significantly enhance methane hydrate growth kinetics as compared to pure water for both experimental and MD simulation runs. Final gas consumption with 1 wt % L-histidine was found to be comparable to that with 1 wt % SDS, the most commonly used additive for hydrate promotion studies. L-histidine is a benign additive which offers considerable enhancement in methane hydrate formation kinetics and can be utilized for various hydrate based technologies such as methane storage and transport. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Amino acid; Crystal growth; Gas hydrate; kinetics; Molecular dynamic simulation

Molecular phylogeny, structure modeling and in silico screening of putative inhibitors of aerolysin of Aeromonas hydrophila EUS112 - Yadav, Sunita Kumari; Panwar, Deepak; Singh, Ankita; Tellis, Meenakshi B.; Joshi, Rakesh Shamsunder; Dixit, Aparna (Journal of Biomolecular Structure & Dynamics, 2022)
Aeromonas hydrophila, a Gram-negative bacterium, causes diseases in fish, resulting in excessive loss to the aquaculture industry. Aeromonas is a highly heterogeneous group of bacteria, and the heterogeneity of the genus is attributed to variation and diversity in the virulence factors and toxins among various Aeromonas strains. One of the major toxins aerolysin, secreted by the bacterium, causes hemorrhagic-septicemia and diarrhea and can serve as a drug target. Here, we describe characterization, molecular phylogeny, and homology modeling of the aerolysin of A. hydrophila strain EUS112 (Ah(EUS112)) cloned in our lab. The encoded aerolysin is 485 amino acids long with an N-terminal signal sequence of 23 amino acids. Phylogenetic analysis of the aerolysin of Ah(EUS112) revealed that it belongs to a diverse group of toxins, showing maximum similarity with aerolysins of other Aeromonas strains followed by Vibrio toxin. The homology model of the mature aerolysin of Ah(EUS112) was generated using the crystal structure of a mutant aerolysin (PDB#3g4n) as the template, which showed that the encoded aerolysin exists as a channel protein. Validation of the generated model using bioinformatics tool confirmed it to be a good quality model that can be used for drug design. Molecular dock analysis revealed that drugs, aralia-saponin I, cyclamin, ardisiacrispin B, and aralia-saponin II bind to aerolysin with a higher affinity as compared to other drugs and at functionally important amino acids of aerolysin. Hence, these molecules can act as an effective therapeutics for inhibiting the aerolysin pore formation and curtail the severity of Aeromonas infection. Communicated by Ramaswamy H. Sarma
Keywords: Aerolysin; homology modeling; Molecular docking; Molecular dynamic simulation; phylogenetic tree

Multi-dimensional impact of captopril modification on human serum albumin - Ghosh, Amrita; Jani, Vinod; Sonavane, Uddhavesh; Naphade, Anvi N.; Joshi, Rajendra; Kulkarni, Mahesh J.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2024)
Captopril is a thiol drug, widely used for the management of hypertension and cardiovascular diseases. Reactive thiols are found to covalently modify the cysteines of plasma proteins and affect their structure and function. Human serum albumin (HSA) is prone to undergo modification by various low molecular weight compounds, including drugs. Cysteine34 (Cys34) in HSA has a free thiol group with antioxidant properties, considered to be the most redox-sensitive amino acid in plasma. Through mass-spectrometric analysis, we demonstrate for the first time that captopril forms a disulfide adduct at Cys34 residue and increases the protease susceptibility of HSA to trypsin. As evidenced by our biophysical and electron microscopy studies, HSA undergoes structural alteration, aggregation and morphological changes when treated with different captopril concentrations. Molecular dynamics studies further revealed the regions of secondary structural changes in HSA due to disulfide adduct formation by captopril at Cys34. It also elucidated the residues involved in the noncovalent interactions with captopril. It is envisaged that structural change in HSA may influence the efficacy of drug delivery as well as its own biological function. These findings may thus provide significant insights into the field of pharmacology intriguing further investigation into the effects of long-term captopril treatment.
Keywords: Captopril; Electron microscopy; Human serum albumin; Mass spectrometry; Molecular dynamic simulation; Spectrophotometry